The Effect of Risk Factors on Auditors' Configural Information Processing - Maletta, Mario J.; Kida, Thomas (The Accounting Review, 1993)
[Recent audit studies by Brown and Solomon (1990, 1991) reveal that careful consideration of domain-specific knowledge can result in the experimental detection of configural relationships between information cues. These findings suggest that auditors' decisions may be more complex than indicated by some previous research, and that additional research is necessary to identify conditions in which auditors utilize configural processes. This study investigates the role of environmental risk factors on the configurality of audit decisions. That is, we test whether the systematic consideration of audit risk variables results in the identification of higher order, interactive decision processes where linear relationships have previously been detected. The findings of Libby et al. (1985) and existing audit pronouncements are used to develop hypotheses regarding auditors' internal audit decisions. The hypotheses concern (1) the interactive effect of inherent risk and control strength on the extent to which auditors rely on internal audit functions to reduce planned audit work and (2) the extent to which these environmental factors affect consideration of three components of internal audit quality: objectivity, competence, and work performed. Audit managers from a Big Six accounting firm responded to a series of audit-planning cases concerning the receivables cycle of a mediumsized manufacturing firm. Inherent risk and strength of control architecture were manipulated as between-subject variables, while the objectivity, competence, and work of the internal auditors were manipulated within subjects. The results indicate that specific audit decisions are quite complex when elements of the risk environment are explicitly considered. Specifically, reliance on the internal audit function was based on a configural relationship between the levels of inherent risk and control strength. Auditors relied more on internal auditors when control architecture was strong rather than weak in conditions of high inherent risk. However, the effect of control architecture was mitigated when inherent risk was low. Also, complex relationships existed between environmental risk and task-specific components of internal audit quality. For example, auditors considered all three internal audit components when making reliance decisions in the high inherent risk and strong control strength condition, but not in certain other risk conditions. Implications of the experimental results are discussed.]